Solar-activated Zinc Oxide Photocatalytic Treatment of Oil Produced Water - Lakkimsetty, Nageswara Rao; Karunya, S.; Varghese, M. J.; Shaik, Feroz (Technological Innovation in Engineering Research Vol. 3, 2022)
For the treatment of oil-produced water, the research study relies on photo catalytic technologies combined with nanochemicals. Solar energy is considered to be the finest option for treating oil generated because it is abundant and available across the Sultanate of Oman all year. In recent years, the photo catalytic method has demonstrated considerable potential as a low-cost, long-term treatment that is also ecologically beneficial. Because of its strong photo catalytic activity, photo-stability, broad band gap, and low toxicity, zinc oxide (ZnO) is utilized as a photocatalyst, and its photo catalytic activity to destroy organic contaminants in oil generated water was explored. As per the experimental study it was observed that ZnO used as a potential catalyst in treating wastewater. The performance of the ZnO was studied by different parameters such as, pH, TDS, conductivity, salinity, DO, TOC and COD. The results showed that TOC was decreased in first 3 hrs and thereafter it remains stable and hence 3 hours is considered as optimum reaction time. However, it was noticed that continuous decrease in COD and turbidity for 5 hrs of exposure under solar radiation.